The effect of the mycotoxin moniliformin on a-keto acid dehydrogenase complexes - Gathercole, P. S.(Patricia Sarah) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc. Biochem.) -- University of Stellenbosch, 1984.